2010 IEEE Frontiers in Education Conference (FIE) 2010
DOI: 10.1109/fie.2010.5673434
|View full text |Cite
|
Sign up to set email alerts
|

Integrative learning in a Synthesis and Design Studio: A phenomenological inquiry

Abstract: Engineering education is uniquely qualified to make strides towards both a more integrated curriculum and understanding the benefits of an integrated learning experiences, due to the vast amounts of experience with innovative integrative curricular structures. This paper briefly describes an innovative approach to integrate student learning through a four year Synthesis and Design Studio.This provides the context for a phenomenological research study that investigated the nature of students' integrative learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This study involves examining emotion and triggers from the student perspective within the context of an interdisciplinary, project-based design studio as implemented in 2009 and 2010. [9][10][11][12] The design studio occurs annually throughout the four-year environmental engineering undergraduate degree. The studio, its attributes, its curricular design, and research concerning student creativity is explored in more depth in other papers, [9][10][11][12] but for the purposes of this short paper it has the following attributes: 1) project-based, 2) deliberate reflective activities, 3) distributed cognition, and 4) studio environment with two, three hour sessions per week.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This study involves examining emotion and triggers from the student perspective within the context of an interdisciplinary, project-based design studio as implemented in 2009 and 2010. [9][10][11][12] The design studio occurs annually throughout the four-year environmental engineering undergraduate degree. The studio, its attributes, its curricular design, and research concerning student creativity is explored in more depth in other papers, [9][10][11][12] but for the purposes of this short paper it has the following attributes: 1) project-based, 2) deliberate reflective activities, 3) distributed cognition, and 4) studio environment with two, three hour sessions per week.…”
Section: Contextmentioning
confidence: 99%
“…A deeper understanding of the integral role of emotion in cognition within engineering education promises to have implications for critical thinking, life-long learning, and motivation. The purpose of this paper is to uncover the role of emotion in learning within an integrated curricular experience [9][10][11][12] and to further understand the interaction of emotion and student learning. This qualitative research study involves a phenomenological, narrative analysis of data collected over two semesters of an interdisciplinary design studio to identify the types of Page 22.1560.2 emotions described, how the emotions evolved over time, and the relationship between emotions and learning.…”
Section: Introductionmentioning
confidence: 99%
“…The pre and post quantitative data indicated that students were more creative after engaging in the transdisciplinary design studio 1 and the qualitative data supported this outcome with focus groups and written reflections that were analyzed using phenomenological approaches. 2 I took some of the previously collected data and tested the idea of using narrative analysis as a way of uncovering important stories that could have strong implications for the research study and for the readers. 3 Narrative analysis promised to be powerful in helping us make sense of complexities inherent in engineering education systems and in resonating with the consumers of our research.…”
mentioning
confidence: 99%